Educação de surdos: desafios para o ensino da língua brasileira de sinais na rede regular de ensino - ROCHA, Bruno Santos (2025)
This work aims to analyze the challenges for the teaching of the Brazilian Sign Language to deaf students in the regular education network. Addresses aspects related to education of the deaf and the Brazilian Sign Language - LIBRAS as mother tongue of the deaf, pointing out the challenges for teaching practice in the teaching of pounds. The research is bibliographic and documentary. The data were collected and systematized from academic and scientific productions that deal with the theme, using the theoretical contributions of Ribeiro (2019), Lacerda (1998), Mantoan (2004), Brasil (1988; 1996; 2015), among others, who dialogue about the theme in question. The results indicate that teaching practice for the teaching of Libras is still surrounded by numerous challenges, such as the implementation of public policies, lack of continuing education, materials and pedagogical methods to work with deaf students. Therefore, it is concluded that the challenges are both in access and in the permanence of these deaf students in regular school.